Geschichte als Element antiker Kultur. Die Griechen und ihre Geschichte(n) - Gehrke, Hans-Joachim (Münchner Vorlesungen zu Antiken Welten, 2014)
The relationship between conceptions of history and forms of political organization has been almost completely neglected in the study of ancient Greek Culture so far. This book shows that an important element of social self-affirmation lays in this very relationship, facilitating a proper assessment of the importance of Greek historiography, and thus casting an entirely new light on a key phenomenon of ancient culture.